Snapshots About East Africa’s Education System: Reviews from Primary School Students and College Students About the Spirit of Fair Play - Hideg, Gabriella (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
This paper focuses on the East African country, Kenya, and its education system, which is exotic from the Hungarian point of view. The aim of my study was to present the historical development of education in Kenya, and the odds and limits appearing within it, based on the available literature. It becomes visible that access to education is not given equally to everyone, regardless of which level of education we examine. This becomes really interesting and unique if we ask primary school students and college students about fair play and its content in such an imbalanced and even unequal system. As a test method, I used the analysis of literature and a questionnaire survey, which was based on a random sampling method. The questionnaire contains 17 questions including 15 closed and 2 open questions. Questions covers the content of fair play, interest in sport, and in addition to these, the responses about behaving in different competitive situations and judging actions as well. The data obtained were summarized with simple mathematical and statistical methods. As an expected result, we get closer to a foreign, unknown country in an educational/ historical and pedagogical point of view. The results of the questionnaire survey, which measure the segments of the two different levels of the Kenyan education system, show the opinion of students about fair play.